Influence of Rock Strength on the Propagation of Slotted Cartridge Blasting-Induced Directional Cracks - Yun Shu; Peng Shao; Chao Dong; Zhen Cao; Xinwei Yi (Advances in Civil Engineering)
Based on theories of explosive mechanics and rock fracture mechanics, the influence mechanism of rock strength on the propagation length of the primary crack in the directional fracture blasting with slotted cartridge has been investigated deeply to propose the relation equation between the rock strength and the propagation length of the primary crack. Theoretically, the maximum length am of the primary crack increases with the enhancing rock strength parameters. The explicit dynamic analysis software LS-DYNA has been used to simulate the slotted cartridge blasting in the mudstone, sandstone, and granite with different strengths in order to reveal the effect of rock strength on the propagation length and velocity of the primary crack and the stress distribution characteristics in rock. The numerical results show the primary crack easily bifurcates and attain a much shorter propagation length in the mudstone with the minimum strength, and there are radial cracks appearing in the nonslotted direction. When rock strength rises, the propagation length, velocity, and duration of the primary crack and the concentration degree of effective stress in the slotted direction will all increase in the sandstone and granite, but there is an opposite influence trend of rock strength in the stage of the initial guide crack’s formation. The cracking velocity has an overall oscillation downtrend whose swing amplitude enhances clearly with the increasing rock strength, signifying the more unsteady propagation of the primary crack in the higher strength rock.